Peptide-Labeled Near-Infrared Quantum Dots for Imaging Tumor Vasculature in Living Subjects - Cai, Weibo; Shin, Dong-Woon; Chen, Kai; Gheysens, Olivier; Cao, Qizhen; Wang, Shan X; Gambhir, Sanjiv S; Chen, Xiaoyuan (Nano letters, 2006)
We report the in vivo targeting and imaging of tumor vasculature using arginine-glycine-aspartic acid (RGD) peptide-labeled quantum dots (QDs). Athymic nude mice bearing subcutaneous U87MG human glioblastoma tumors were administered QD705-RGD intravenously. The tumor fluorescence intensity reached maximum at 6 h postinjection with good contrast. The results reported here open up new perspectives for integrin-targeted near-infrared optical imaging and may aid in cancer detection and management including imaging-guided surgery.